THE EFFECT OF ATTACHMENT AND BREASTFEEDING SELF-EFFICACY ON MOTHERS' EXCLUSIVE BREASTFEEDING BEHAVIOR - Togi Fitri A Ambarita; Asina Christina Rosito; Gloria (RADJA PUBLIKA, 2025)
Exclusive breastfeeding achievement is still a national problem, thus it is important to conduct studies related to breastfeeding behavior, particularly studying of mental or psychological aspects. This study aims to explain the influence of maternal attachment and breastfeeding self-efficacy (BSE) on exclusive breastfeeding behavior. The research method uses quantitative techniques, using binary logistic regression tests. Data collection techniques use attachment scales, BSE scales and maternal breastfeeding behavior questionnaires. Reliability tests with Cronbach alpha are certain: attachment scale = 0.883 and BSE scale = 0.921. The results of the study prove that there is a joint influence of attachment and BSE variables on exclusive breastfeeding behavior. The influence given is 14.9%. However, the analysis of the influence of each independent variable (X1 and X2) on Y (independent) shows that the BSE variable has a significant effect on exclusive breastfeeding behavior, while the attachment variable does not have a significant effect on exclusive breastfeeding behavior.